The daily covid-19 information from the publics’ lens - Ahmad, Zeti Azreen; Buyong, Mazni; Souket, Rizwanah (2021)
COVID-19 pandemic has imposed an unprecedented impact to people around the globe and Malaysia is not excluded. The cumulative cases of COVID-19 in the country as of September 16, 2021 has exceeded two million with more than 20,000 fatalities. The battle to fight the unseen virus came along with infodemic; a massive amount of information that include a mixture of true and false narratives that make intervention efforts to be even more complicated. The role of the Ministry of Health (MoH) has been instrumental in managing the pandemic and infodemic in Malaysia. The ministry has laid down all preventive measures including a total lockdown to contain the virus. The Director General of Health (DG), has never failed to update the public and the media through press conferences and press statements since the first few cases of COVID-19 were reported in the early of January 2020. Daily statistics of COVID-19 cases are also uploaded in MoH’s website and social media platforms. In recent development, detailed of COVID-19 cases is now reported in a new website known as CovidNow. This research is developed based on an ideal yet very important premise. Living with a fatal pathogen such as SARS-CoV-2 requires every person to have access to trustworthy information about the disease and able interpret the information accurately leading to the right action to mitigate risk. However, the publics’ ability to interpret scientific information such as COVID- 19 did not receive adequate attention. It is worth noted that publics’ interpretation of COVID-19 is not free from biases thus, a sound scientific literacy is fundamental. This study aims to explore on publics’ perception of the daily COVID-19 update. It will examine whether the information shared by MoH was comprehensible, perceived useful and improve the publics’ scientific literacy about the disease. This study argues that a sound scientific literacy will enable the publics to question, investigate and draw evidence-based conclusion about COVID-19 and subsequently empower them to protect themselves and others. This study will initiate an online survey nationwide to obtain data from the public. Findings of this research will assist policy makers and public health officials to improve their communication strategies in their attempts to educate and empower the publics to take the right action during a severe public health crisis. COVID-19 will soon become an endemic that requires everyone to remain vigilant to protect themselves and their loved ones. As the virus will continue to stay, public’s awareness, understanding and scientific literacy about the disease ought to be enhanced. At this stage, scientific literacy is no longer ideal but a critical goal to achieve to continue with life.